A gaint thrombosed isolated femoral artery aneurysm: a rare entity - Reddy, Gajulapalli Prudhvi Vardhan; Shrotriya, Siddhant; Pathak, Nitin J. (International Surgery Journal, 2020)
A 70-year-old woman was admitted to the hospital due to a swelling on her right inner thigh that was evident for six months. She had a history of trauma few months back, also history of stroke on anti-platelet treatment. Ultrasound of thigh suggestive of thrombosis in right femoral artery. Doppler suggestive of aneurysm of right femoral artery with thrombus. Right femoral artery aneurysm excision and thrombectomy done.